A human case of tick bite by Ixodes persulcatus - Im, K; Lee, I Y; Lee, W J (Korean journal of parasitology, 1998)
The first case of tick bite by Ixodes persulcatus in Korea is reported. The tick was found on the skin of right lower axilla region of a 60-year-old woman.The first case of tick bite by Ixodes persulcatus in Korea is reported. The tick was found on the skin of right lower axilla region of a 60-year-old woman.